The Experience of Living With Breast Cancer and the Assessment of Needs and Expectations - Maria Nikoloudi MD; Florjan Thanasko PhD; Efi Parpa MA, PhD; Sotiria Kostopoulou RN, MSc; Kyriaki Mystakidou MD, PhD (Journal of Patient Experience, 2021)
Living with a chronic disease constitutes a biographical reversal characterized by change and loss. The aims of this study are to conceptualize the meaning of breast cancer, of its burden, to explore the patient's needs and expectations while being admitted to a palliative care unit, and to evaluate the fulfillment of those expectations. Two semistructured interviews were conducted, audio taped, transcribed verbatim, and subjected to the qualitative method of Interpretative Phenomenological Analysis. The first interview was conducted at the first visit of the patient to the palliative care unit, and the second after 2 weeks of receiving palliative care services. Qualitative findings indicated that the meaning of cancer can be interpreted as a transition of fading away. The transition began with redefining cancer from “my difficult moment” to “fortunately to its final destination”; struggling with the paradox of “the will to see the development of yourself and your child” and “wishing to die” while being able to “adapt” to “a balanced” day to day leaving and preparing for death. The need for interdisciplinarity is expressed.